PENGARUH METODE PEMBELAJARAN PEMECAHAN MASALAH DAN GAYA KOGNITIF TERHADAP HASIL BELAJAR MATEMATIKA - Nurhayati Na; Khasanah Khasanah (Akademika : Jurnal Teknologi Pendidikan, 2018)
This study aimed to determine : ( 1 ) The difference in student learning outcomes treated with problem-solving learning method is higher than student learning outcomes treated with expository teaching methods , (2 ) interaction between learning method with cognitive style on learning outcomes of mathematics ; ( 3 ) the results of the mathematical learning of students who have cognitive style field independence givenlearning problem-solving methods of treatment is higher than the expository method , (4 ) the results of the mathematical learning of students who have cognitive style field dependence given treatment expository teaching method is higher than the problemsolving methods . The hypothesis in this study were 1 ) There are differences in student learning outcomes treated with the methods of learning and problem solving expository teaching methods ; 2 ) There is an interaction between cognitive styles and teaching methods on learning outcomes of mathematics ; 3 ) mathematics learning outcomes of students who have cognitive style field independence given learning problem-solving methods of treatment is higher than the expository method ; 4 ) mathematics learning outcomes of students who have cognitive style field dependence given treatment expository teaching method is higher than the methods of solving problems . The targetpopulation is the entire fourth grade students SDIT Al - Izzah Serang Banten which totaled 173 students . Samples were taken with a random sampling technique that randomly select each of the two ( 2 ) classes to be treated with the use of teaching methods and classroom problem solving using learning methods usedekspositori.Instrumen untukmendapatkan data through student learning outcomes variable ( Y ) using tests of cognitive learning outcomes , cognitive style variables using tests of cognitive style Group embedded Figures test ( GEFT ) . The results showed that : First , the results of student learning using a problem -solving method of teaching is higher than that using the expository method , value sig = 0.009 < α = 0.05 . Second ,there was an interaction between cognitive styles and learning methods , Value sig = 0.00 < α = 0.05 , F value = 5.168 > F = 3.99 . Third , mathematics learning outcomes of students who have cognitive style field independence given learning problem-solving methods of treatment is higher than the expository method , with the results Qhitung > Qtabel ( 4.55 > 2.95 ) . Mathematics learning outcomes of students who have thecognitive style of field dependence given treatment expository teaching method is higher than the methods of solving problems , with the result Qhitung > Qtabel (3.03 > 2.95 )